(untitled) (Research, Society and Development, 2022)
Objective: To analyze the factors associated with the high prevalence of iron deficiency anemia in children up to 5 years of age, how the disease is diagnosed and its treatment. Methodology: A literature review was carried out, carrying out a survey of the main factors associated with the high prevalence of iron deficiency anemia in children, as possible indicators of nutritional and food insecurity. Results: Iron deficiency anemia is a public health problem that mainly affects children up to 5 years of age, considered a vulnerable group due to the increased demand for iron triggered by the intense speed of growth and development at this stage. This nutritional deficiency results from the imbalance between the amount of bioavailable iron absorbed in the diet and the need for the mineral in the body and is directly associated with factors such as socioeconomic level, environmental, nutritional and biological factors. Anemia intervenes in the development of children and can cause several damages to health, being of extreme importance its diagnosis and treatment. Final considerations: The occurrence of anemia has multifactorial causes and can cause several damages in child development and for all these aspects, it is extremely important to implement preventive measures, aiming at the orientation of the population and the consumption of adequate foods.